Russian futurist theatre theory and practice - Leach, Robert 1942- (Edinburgh critical studies in modernism, drama and performance, 2020)
Russian Futurist Theatre explores is the first book to comprehensively uncover the Russian futurist theatre in all its virtuosity and diversity